A novel anatomical integrated acetabular plate for acetabular fracture involving posterior wall/column: a biomechanical study - Pei, Xuan; Chen, Yu; Fang, Zhixun; Xiong, Ziren; Chen, Jianan; Zheng, Yifan; Wang, Ting; Qian, Shenglong; Chen, Long; Wang, Guodong; Qi, Jing; Liu, Ximing (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionThe optimal treatment for complex acetabular fracture involving the posterior wall and column remains controversial. To address this issue, a novel anatomically integrated acetabular plate (AIP) was developed, designed to integrate the biomechanical advantages of both reconstruction and T-shaped plates. This biomechanical study aimed to evaluate the mechanical performance of the AIP in comparison with conventional fixation methods.MethodsAcetabular fractures involving the posterior wall and column were created in 18 fresh-frozen pelvis specimens and assigned to three fixation groups: (1) an anatomically integrated plate (AIP), (2) two reconstruction plates with a T-plate (RPTP), and (3) two reconstruction plates with two lag screws (RPLS). A standing position was simulated, and a Zwick Z100 testing machine applied an axial load from 0 to 1400 N. A load-displacement sensor and digital dial gauge were used to measure overall displacement, stiffness, and displacement of the posterior wall and column to evaluate the mechanical stability of each fixation construct.ResultsUnder increasing axial loading, all three groups of model specimens exhibited a linear trend in axial displacement without sudden load drops. Among the groups, the AIP group demonstrated the smallest overall displacement (1.87 ± 1.09 mm), followed by the RPTP (2.29 ± 1.12 mm) and RPLS groups (2.63 ± 1.21 mm). No significant difference in displacement was observed between the AIP and RPTP groups under loads of 0–1000 N (P > 0.05), whereas a significant difference emerged at higher loads of 1200–1400 N (P < 0.05). Under a peak load of 1400 N, the axial stiffness followed the trend: Normal (NOR) group > AIP group > RPTP group > RPLS group, with mean stiffness values of 356.10 ± 12.33 N/mm, 339.87 ± 21.86 N/mm, 302.04 ± 13.69 N/mm, and 266.32 ± 9.16 N/mm, respectively. The AIP group exhibited significantly higher stiffness than both the RPTP and RPLS groups (P < 0.05), with no significant difference between the AIP and NOR groups (P > 0.05). Furthermore, the AIP group showed significantly lower displacement of the acetabular posterior wall and column compared to the RPTP and RPLS groups (P < 0.05). Notably, two specimens in the RPLS group showed posterior wall displacements exceeding 2 mm, which met the criteria for internal fixation failure.ConclusionOverall, the AIP group provided the best biomechanical performance in terms of minimizing displacement and maximizing stiffness, followed by RPTP and RPLS group, indicating its potential superiority for the stabilization of acetabular fractures involving the posterior wall and column.